2015
DOI: 10.1111/cogs.12244
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Social Network in Dreams: Transitivity, Assortativity, and Giant Component Proportion Are Monotonic

Abstract: For five individuals, a social network was constructed from a series of his or her dreams. Three important network measures were calculated for each network: transitivity, assortativity, and giant component proportion. These were monotonically related; over the five networks as transitivity increased, assortativity increased and giant component proportion decreased. The relations indicate that characters appear in dreams systematically. Systematicity likely arises from the dreamer's memory of people and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…The most important new adult content findings, reported by mathematical psychologists, demonstrate that the social networks in dreams are very similar to those in waking life. They are small-world networks that have the same properties that are also found in studies of brain networks, memory networks, and many aspects of the social and natural worlds, which is evidence that dreams are more lawful than has previously been thought (Han, 2014;Han, Schweickert, Xi, & Viau-Quesnel, 2016). Then, too, the frequency of appearance of familiar characters in dreams is consistent with Zipf's power law, which is further evidence for the lawfulness of dreams (Schweickert, 2007a(Schweickert, , 2007b.…”
Section: New Findings That Support the Theorymentioning
confidence: 60%
“…The most important new adult content findings, reported by mathematical psychologists, demonstrate that the social networks in dreams are very similar to those in waking life. They are small-world networks that have the same properties that are also found in studies of brain networks, memory networks, and many aspects of the social and natural worlds, which is evidence that dreams are more lawful than has previously been thought (Han, 2014;Han, Schweickert, Xi, & Viau-Quesnel, 2016). Then, too, the frequency of appearance of familiar characters in dreams is consistent with Zipf's power law, which is further evidence for the lawfulness of dreams (Schweickert, 2007a(Schweickert, , 2007b.…”
Section: New Findings That Support the Theorymentioning
confidence: 60%
“…For her parents, “my mother” and “my father” were used as queries since ^my mother^ outputs all dreams with “my” or “mother.” These two characters were the only characters with more than one word. Her mother and father, the only characters not called by their names, were also searched for using “my parents.” The dreamer was not coded as a character, as in the Hall and Van De Castle (1966) system (see Han, Schweickert, Xi, & Viau-Quesnel, 2016, for a discussion). For each query, DreamBank.net returns dream numbers for the dream reports where the query is in, and shows the dream reports with highlighted matches.…”
Section: Methodsmentioning
confidence: 99%
“…Turning again to the similarities between the Izzy and Jasmine findings, they are also similar in that they dreamed most frequently about their mothers, and both of them considered their mother to be the person they would turn to in waking life if they needed comfort, even though Izzy repeatedly mentioned that she did not have a warm or close relationship with her mother, especially in her preadolescent and early teenage years. In keeping with this finding, a study using network techniques to examine character networks in five different dream series revealed that there was always one character that stood out as the most central character in the dreamer’s mental social network (Han, Schweickert, Xi, & Viau-Quesnel, 2016).…”
Section: Resultsmentioning
confidence: 88%